In vivo knockdown of basal forebrain p75 neurotrophin receptor stimulates choline acetyltransferase activity in the mature hippocampus. Issue 5 (11th February 2016) - Barrett, Graham L.; Naim, Timur; Trieu, Jennifer; Huang, Mengjie
Abstract : This study seeks to determine whether knockdown of basal forebrain p75 neurotrophin receptor (p75 NTR ) expression elicits increased hippocampal choline acetyltransferase (ChAT) activity in mature animals. Antisense (AS) oligonucleotides (oligos) targeting p75 NTR were infused into the medial septal area of mature rats continuously for 4 weeks. In all rats, the cannula outlet was placed equidistant between the left and the right sides of the vertical diagonal band of Broca. We tested phosphorothioate (PS), morpholino (Mo), and gapmer (mixed PS/RNA) oligos. Gapmer AS infusions of 7.5 and 22 μg/day decreased septal p75 NTR mRNA by 34% and 48%, respectively. The same infusions increased hippocampal ChAT activity by 41% and 55%. Increased hippocampal ChAT activity correlated strongly with septal p75 NTR downregulation in individual rats. Infusions of PS and Mo AS oligos did not downregulate p75 NTR mRNA or stimulate ChAT activity. These results demonstrate that p75 NTR can dynamically regulate hippocampal ChAT activity in the mature CNS. They also reveal the different efficacies of three diverse AS oligo chemistries when infused intracerebrally. Among the three types, gapmer oligos worked best. © 2016 Wiley Periodicals, Inc. Abstract : Gapmer oligos allowed us to downregulate the p75 neurotrophin receptor in the medial septum and the vertical limb of the diagonal band of Broca. As hypothesized, and in agreement with data from the heterozygous and homozygous p75 knockout mice, this brought about substantial enhancement of hippocampal cholinergic acetyltransferase activity in normal, adult rats.